2023
DOI: 10.1136/bmjopen-2022-068350
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of steerable versus non-steerable sheaths for catheter ablation of atrial fibrillation systematic review and meta-analysis

Xinyao Jin,
Yuqing Zhou,
Yuanhong Wu
et al.

Abstract: ObjectivesWith the development of radiofrequency (RF) ablation technology. In recent years, more and more patients with atrial fibrillation (AF) have been treated with RF ablation. Steerable sheaths (SS) have been widely used in RF ablation of AF. The aim of this meta-analysis was to compare the efficacy and safety of AF ablation using SS and non-steerable sheaths (NSS).MethodsFrom the beginning to March 2022, we conducted a comprehensive, systematic search of the databases PubMed, MEDLINE, EMBASE, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It concluded that steerable sheaths can effectively reduce the recurrence rate of AF and the occurrence of acute PVs reconnection events. However, there is no advantage in shortening the total RF time, fluoroscopy time, total surgical time and reducing complications (35). Considering that our study aimed to evaluate the complications and long-term results, using the steerable sheath might influence the recurrence rate but not the other parameters reported in our results.…”
Section: Long-term Outcome After Af Catheter Ablationmentioning
confidence: 83%
“…It concluded that steerable sheaths can effectively reduce the recurrence rate of AF and the occurrence of acute PVs reconnection events. However, there is no advantage in shortening the total RF time, fluoroscopy time, total surgical time and reducing complications (35). Considering that our study aimed to evaluate the complications and long-term results, using the steerable sheath might influence the recurrence rate but not the other parameters reported in our results.…”
Section: Long-term Outcome After Af Catheter Ablationmentioning
confidence: 83%